Prevalence of Wheat Associated Bacillus spp. and Their Bio-Control Efficacy Against Fusarium Root Rot - Mulk, Shah; Wahab, Abdul; Yasmin, Humaira; Mumtaz, Saqib; El-Serehy, Hamed A.; Khan, Naeem; Hassan, Muhammad Nadeem (Frontiers in Microbiology, 2022)
Bacillus spp. are the most prevalent group of bacteria in nature. Their prevalence depends upon multiple factors viz sporulation, antagonism, and production of secondary metabolites. Fusarium root rot is the most common disease of wheat. The development of an eco-friendly approach to cope with edible crops diseases is very substantial for humans. In the present study, 658 isolates were obtained from wheat grown in the wheat rice cropping system and tested for their antagonistic activity against four wheat root rot pathogens. viz Fusarium oxysporum, Fusarium moniliforme, Macrophomina phaseolina and Rhizoctonia solani. Out of 658, 106 isolates were found antagonistic to either single or multiple fungi. Out of 106 antagonistic bacteria, 62 (23%) were rhizospheric, 28 (14%) were root endosphere and 16 (9%) were leaf endosphere. Based on mean inhibition against all fungi, the bacterial strains SM-39 and SM-93 showed maximum antagonistic activity. The 16S rRNA gene analysis revealed that the majority of the antagonistic bacteria exhibiting ≥48% antagonism were Bacillus spp. (98%), except two were Klebsiella spp. (2%). The bacterial strains exhibited phylogenetic lineage with the type strains of the respective genus based on the 16S rRNA gene sequences. In the net house experiment, Bacillus velezensis (SM-39) and Bacillus cabrialesii (SM-93) significantly suppressed Fusarium root rot severity in wheat (42-62 %). Plants treated with these strains have lower electrolytic leakage (29-36 %), as compared to untreated (44%). Relative water content was much higher (46-58%) for plants inoculated with these strains. These antagonistic strains also considerably colonized the wheat rhizosphere with a cells population of 5.8-6.9.log CFU/g of soil.